Pneumatic membranes for biogas plants - Beccarelli, Paolo; Maffei, Roberto (IASS, 2018)
The biogas sector had a rapid development in the last decade with several new industrial plants realized all over Europe and Worldwide. The intrinsic efficiency of membrane structures [1] provided a cost effective solution to cover digesters, bio-filters, lagoons and gas holders through different concepts such as floating membranes, anticlastic geometries and pneumatic structures. However, after less than ten years of use, the structures show several critical aspects, generally related to the premature corrosion of the membrane, the failure of the joints and the overload due to strong winds and heavy snowfalls. This paper presents a review of the main structural solutions based on a pneumatic concept such as air-halls, pneumatic beams and floating roofs. The description will be supported by case studies of each type of structure including air-halls for digesters and bio-filters, Tensairity® and pneumatic beams for long span roofs, floating roofs for large lagoons. For each case study the authors will present data and examples related to the design, manufacturing and installation of the membrane and the issues related to the rapid degradation of the performance of the structure due to the extreme corrosive environment based on high temperatures and high concentration of corrosive chemicals. Finally, the paper will offer a review of the current precautions and solutions to reduces the risks of failures and to improve the expected lifespan of the structures.